Energizing Performance of Sports Energy Drinks - Vasudeo Zambare (Nepal Journal of Biotechnology)
In the dynamic realm of sports and fitness, the role of nutrition is pivotal. Among the various supplements that have gained prominence, sports energy drinks stand out as a powerful tool to fuel athletic performance. As athletes and fitness enthusiasts increasingly turn to these beverages, it’s essential to explore the dynamics behind sports energy drinks, their ingredients, benefits, and the considerations that come with their consumption.